INVESTIGATING CHOLAGOGUE AND CHOLERETIC ACTIVITY OF PEUMUS BOLDUS - Raphael S. F. Silva; Marcus Vinícius H. Faria; Joyce F. S. D. de Almeida; Tanos C. C. França (Química Nova)
This study aimed to utilize molecular modeling and theoretical chemistry methods to contribute to the elucidation of the mechanism of action of boldine, an alkaloid present in the Peumus boldo plant. Boldo holds a special place in traditional medicinal practices throughout Brazil and has been officially recognized as medicinal plant. It is traditionally indicated for choleretic and cholagogue effects, among other digestive disorders. Literature has provided experimental evidence demonstrating that boldine can bind to the farnesoid X receptor, a key player in the production and excretion of bile. Our in silico study revealed that boldine exhibits stable non-bonded interactions like those calculated for the endogenous ligand chenodeoxycholic acid and the synthetic agonist colifexor, supporting what has been experimentally observed in the literature. The packages MOPAC, AutoDock, GROMACS and g_mmpbsa were employed for structural optimization, molecular docking, molecular dynamics and bond energy calculations respectively. This study demonstrates the application of theoretical chemistry and molecular modeling methods, including molecular docking, molecular dynamics, and molecular mechanics Poisson-Boltzmann surface area (MM-PBSA), in identifying molecular targets and providing insights into the bioactivities of natural products.